Impact of the COVID-19 pandemic and COVID vaccination campaign on imaging case volumes and medicolegal aspects - Battaglia, Caterina; Manti, Francesco; Mazzuca, Daniela; Cutruzzolà, Antonio; Corte, Marcello Della; Caputo, Fiorella; Gratteri, Santo; Laganà, Domenico (Frontiers in Health Services, 2024)
Purpose The coronavirus pandemic (COVID-19) significantly impacted the global economy and health. Italy was one of the first and most affected countries. The objective of our study was to assess the impact of the pandemic and the vaccination campaign on the radiological examinations performed in a radiology department of a tertiary center in Southern Italy. Materials and methods We analyzed weekly and retrospectively electronic medical records of case volumes performed at the Radiology Department of “Mater Domini” University Hospital of Catanzaro from March 2020 to March 2022, comparing them with the volumes in the same period of the year 2019. We considered the origin of patients (outpatient, inpatient) and the type of examinations carried out (x-ray, mammography, CT, MRI, and ultrasound). A non-parametric test (Wilcoxon Signed Rank test) was applied to evaluate the average volumes. Results Total flows in the pandemic period from COVID-19 were lower than in the same pre-pandemic period with values of 552 (120) vs. 427 (149) median (IQR) (p < 0.001). The vaccination campaign allowed the resumption of the pre-vaccination pandemic with total flows 563 (113) vs. 427 (149) median (IQR) p < 0.001. In the post-vaccination period, the number of examinations was found to overlap with the pre-COVID period. Conclusion The pandemic impacted the volume of radiological examinations performed, particularly with the reduction of tests in outpatients. The vaccination allowed the return to the pre-COVID period imaging case volumes.